(untitled) (Bangladesh Veterinarian, 2010)
An experiment was conducted for a period of 90 days with twelve local growing bull calves to study the effect of feeding broiler litter (BL) and layer manure (LM) on feed intake, digestibility, live weight gain (LWG) and feed costs. Calves were divided into four groups, three animals in each group and allocated four dietary treatments in a randomized block design. All animals were fed rice straw and green fodder adlibitum and 25% concentrate mixture was supplied. The concentrate mixture of control group A contained mustard oil cake, rice polish, wheat bran, di-calcium phosphate (DCP) and common salt. Instead of mustard oil cake, diet B contained 40% BL, diet C 40% LM, and diet D 20% BL and 20% LM. Differences in weight gain between groups were not significant (p>0.05). Feed conversion efficiency (FCE) of control group A was significantly (p>0.05) better than in group C. and non-significantly better than that of group B. The inclusion of broiler litter and layer manure in the ration did not significantly affect the digestibility of dry matter (DM), organic matter (OM), crude protein (CP), crude fibre (CF) and nitrogen free extract (NFE), but the digestibility of ether extract (EE) was significantly higher (p<0.05) in diet A than in C and D. Cost of meat production was significantly (p<0.05) higher for diet A than for diets B, C and D. DOI: 10.3329/bvet.v25i2.4619 Bangl. vet. 2008. Vol. 25, No. 2, 62-67